The Effect of Supply Chain Management and Machine Maintenance on Production Performance at CV Pabrik Tahu Sumedang - Berlyawan, Ananda Lutfi; Hananto, Djoko (Transpublika Publisher, 2025)
This study aims to analyze the impact of Supply Chain Management (SCM) and machine maintenance on production performance at CV Pabrik Tahu Sumedang. In the food industry, production efficiency is a crucial factor in maintaining business sustainability and company competitiveness. SCM plays an essential role in ensuring the availability of raw materials, smooth distribution, and coordination among parties within the supply chain, thereby optimizing the production process. On the other hand, proper machine maintenance is necessary to maintain operational stability, reduce the risk of equipment failure, and enhance production effectiveness. This research utilizes a quantitative approach by conducting a survey and distributing questionnaires to 54 employees at CV Pabrik Tahu Sumedang. To ensure the reliability of the data, the analysis technique employed is multiple linear regression, starting with validity, reliability, and classical assumption tests. The implications of this study suggest that the company must continuously optimize supply chain management to minimize production constraints, such as delays in raw material supply and distribution inefficiencies. Additionally, the company should implement a more structured machine maintenance strategy, including preventive and corrective maintenance, to ensure machines operate in optimal conditions. By improving SCM and machine maintenance aspects, the company can enhance overall production performance, maintain competitiveness, and meet the growing market demand.